Hair cortisol of pigs in mixed organic farms: the influence of season, breeding system and sex - Nadlučnik, Eva; Vake, Tilen; Šket, Ana; Žižek, Ana; Snoj, Tomaž; Štukelj, Marina (Frontiers in Veterinary Science, 2024)
IntroductionMeasurement of hair cortisol concentration (HCC) is a useful tool for assessing the activity of the hypothalamic-pituitary-adrenal axis and thus evaluating the long-term adrenocortical response in different animal species and breeds. Robust indigenous pig breeds are highly adapted to the local environment and are preferred for organic farming, compared to the commercial breeds. We investigated whether seasonality, breeding system (indoor or outdoor) and sex influence HCC of pigs reared on organic farms.Materials and methodsFifty-three pigs of the indigenous Slovenian Krškopolje breed were divided into three groups. Group Ind (n = 15) was housed indoors, groups Out-1 (n = 18) and Out-2 (n = 20) were housed outdoors on two different farms for the duration of 9 months. Hair was sampled once per season in the withers area of each pig and HCC was determined using a previously validated ELISA.Results and discussionThe effect of seasonality was found to be significant and more pronounced in pigs reared outdoors. HCC were highest and varied most in winter for all groups, while they were lowest and varied less in summer and autumn. The highest HCC was measured in group Out-1 in winter, as it was the only group housed outdoors at that time. Group Ind had significantly higher HCC in summer compared to the groups Out-1 and Out-2, which could be due to hair cortisol degradation by the UV light exposure in outdoor groups. Sex had no effect on HCC. Our study suggests that seasonality and housing type influence the HCC of pigs.